2019
DOI: 10.5539/gjhs.v11n6p169
|View full text |Cite
|
Sign up to set email alerts
|

Arabic Language Surveys Measuring Mothers’ Satisfaction During Childbirth: A Review

Abstract: PURPOSE: To review Arabic surveys used to measure maternal satisfaction. METHODOLOGY: Peer-reviewed studies published in English and Arabic since 2000 were reviewed across eight databases. Surveys were assessed by: survey construction, reliability, and validity. FINDINGS: The seven studies that met the inclusion criteria were in English and included seven different Arabic surveys. Survey items ranged from eight to 32 and were translated from English (3/7) or were originally written in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…For a thorough and reliable evaluation of women’s assessments of their childbirth experiences, it is imperative to employ self-report measures with sound psychometric properties. However, previous reviews have consistently found that most instruments measuring birth satisfaction lack robust psychometric properties and theoretical coherence (Al Nadabi & Mohammed, 2019 ; Sawyer et al, 2013 ). A review of 18 years (2000–2018) identified nine instruments used in Arabic-speaking nations, none of which were applied in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a thorough and reliable evaluation of women’s assessments of their childbirth experiences, it is imperative to employ self-report measures with sound psychometric properties. However, previous reviews have consistently found that most instruments measuring birth satisfaction lack robust psychometric properties and theoretical coherence (Al Nadabi & Mohammed, 2019 ; Sawyer et al, 2013 ). A review of 18 years (2000–2018) identified nine instruments used in Arabic-speaking nations, none of which were applied in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…A review of 18 years (2000–2018) identified nine instruments used in Arabic-speaking nations, none of which were applied in Saudi Arabia. The conclusion was that most of these instruments lacked robust psychometric properties (Al Nadabi & Mohammed, 2019 ). Theoretical coherence, validity, and reliability are essential characteristics of measurement instruments (Sawyer et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%